Diagnóstico estratégico del sistema de gestión del Hotel Islazul, Santa Clara Libre - García Martínez, Xoedy; Gálvez Cabrera, Keisy (Universidad Central "Marta Abreu" de Las Villas, 2008)
El presente trabajo fue realizado en el Hotel Islazul Santa Clara Libre el cual tuvo como objetivo diagnosticar estratégicamente el sistema de gestión para contribuir al perfeccionamiento del mismo con este trabajo se detectaron las necesidades existentes en la instalación hotelera para la posterior puesta en práctica de medidas que aprovechen los puntos fuertes y disminuir las debilidades, mejorando la gestión empresarial. Esta investigación permitirá proveer a los especialistas de esta instalación hotelera de un caudal informativo sobre las diferentes problemáticas que existen en su área de desempeño y que deben eliminar a partir de una proyección estratégica del sistema de gestión que contribuirá al perfeccionamiento y elevación de los resultados de su actividad. Constituye un estudio descriptivo que llega a recopilar datos necesarios, importantes y suficientes, referentes al tema tratado. Se utilizaron métodos del nivel teórico y métodos del nivel empírico como el método de observación, de encuesta, de estudio documental, y el método de trabajo en grupo.

The Strategic Diagnosis of micro, small, and medium, tourist enterprise, constitutes a technique that includes all the enterprise and the surroundings, therefore, when applying the Carlos Martínez Martínez procedure to the Islazul Santa Clara Libre Hotel the result might be the development of the competitive capacity of this kind of installation. In the present work we expose the results obtained with this procedure, which allowed to detect the existing necessities in the hotel installation for the later putting into practice of the strategic measures to become useful the advantages and to reduce the disadvantages, improving the management system. This investigation constitutes a descriptive study that gets to collect necessary, important and enough information referring to this topic. The universe is constituted by workers of this Hotel, the sample is a group of eleven workers. Iselected by means of the theory of chances, which were searched in each of the operation areas in the hotel. We used methods of the theoretical and the empirical level like observation, survey, documentary study, we also included the method of work in groups. This investigation will allow to provide to the different specialists of this hotel installation of an informative volume on its problematic areas, and how to reduce them, from a strategic projection of the management system, which will contribute to theimprovement and elevation of the results of its activity.
Keywords: Economía; Sistema de Gestión; Gestión Empresarial; Perfeccionamiento Empresarial; Hotel Islazul; Santa Clara Libre